2016
DOI: 10.1186/s12871-016-0266-2
|View full text |Cite
|
Sign up to set email alerts
|

Observational study on patterns of neuromuscular blockade reversal

Abstract: BackgroundUsing electronic health record data, we hypothesized that larger reversal doses are used for patients with deeper levels of neuromuscular blockade (NMB) as evidenced by the last recorded TOF measurement. We also examined if dosing regimens reflect current practice guidelines of using ideal body weight (IBW) for NMB agents and total body weight (TBW) for neostigmine.MethodsThis is a retrospective observational study of adult, ASA 1–4 patients who underwent general anaesthesia and received non-depolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Neostigmine was administered to half of all patients where a non‐depolarising NMB drug was given, at a mean dose of 32 µg.kg −1 , but predominantly in doses of a full or half vial, regardless of patient weight. The proportion of patients that received a reversal drug was considerably lower than in an American study where 86% received neostigmine, where only subjective neuromuscular monitoring was available . The use of objective neuromuscular monitoring in our study enabled anaesthetists to omit reversal in cases with spontaneous recovery to a TOF ratio > 0.9.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Neostigmine was administered to half of all patients where a non‐depolarising NMB drug was given, at a mean dose of 32 µg.kg −1 , but predominantly in doses of a full or half vial, regardless of patient weight. The proportion of patients that received a reversal drug was considerably lower than in an American study where 86% received neostigmine, where only subjective neuromuscular monitoring was available . The use of objective neuromuscular monitoring in our study enabled anaesthetists to omit reversal in cases with spontaneous recovery to a TOF ratio > 0.9.…”
Section: Discussionmentioning
confidence: 62%
“…This probably explains the widespread use of a rather small standard dose of one or a half vial of neostigmine. This is in contrast to when only subjective neuromuscular monitoring is available, where it is reasonable to use a weight‐based dosing standard, as was also the case in the American study . In 6% of cases with neostigmine, reversal was administered at a TOF ratio > 0.9.…”
Section: Discussionmentioning
confidence: 96%
“…It is recommended to initiate neostigmine under neuromuscular monitoring as well. However, a recent retrospective study indicated that neither the doses of neostigmine nor the duration to extubation were affected by the depth of the neuromuscular blockade prior to reversal, exposing discrepancies between existing guidelines and the actual clinical practice 63. More evidence are needed if the current concepts of timing of neostigmine administration are to be updated.…”
Section: Administration For Neuromuscular Blockade Reversalmentioning
confidence: 99%